Implementation of Interactive Video in Improving Family-Based Intervention Ability to Parents of Special Needs Students - Meggy, Hendriano; Juhanaini, Juhanaini (International Conference on Elementary Education, 2021)
Pandemic Covid-19 has a huge impact on student learning activities, usually learning is carried out in schools because of the pandemic students are required to study at home. This has a big effect on students with special needs because in school students are served with special programs and have a support teacher, but at home, parents have to do everything. So that parents have a lot to learn how to teach and assess their child's development. However, not all parents can do it because of their limited experience and knowledge. The goal is to improve the ability of parents to intervene with their children with interactive videos. This research method uses a qualitative descriptive method to see the increase in the ability of parents to intervene with their children who have a deficiency. To ensure the accuracy of the data obtained, it can be done by triangulation. Based on the observations of researchers from the data obtained, interactive video can improve the ability of family-based interventions in parents, this is evidenced by the changes that occur in the abilities of children with special needs.